Adolescent Intermittent Alcohol Exposure: Persistence of Structural and Functional Hippocampal Abnormalities into Adulthood. (27th April 2015) - Risher, Mary‐Louise; Fleming, Rebekah L.; Risher, W. Christopher; Miller, K. M.; Klein, Rebecca C.; Wills, Tiffany; Acheson, Shawn K.; Moore, Scott D.; Wilson, Wilkie A.; Eroglu, Cagla; Swartzwelder, H. S.
<x xml:space="preserve">Abstract</x> Background Human adolescence is a crucial stage of neurological development during which ethanol (EtOH) consumption is often at its highest. Alcohol abuse during adolescence may render individuals at heightened risk for subsequent alcohol abuse disorders, cognitive dysfunction, or other neurological impairments by irreversibly altering long‐term brain function. To test this possibility, we modeled adolescent alcohol abuse (i.e., intermittent EtOH exposure during adolescence [AIE]) in rats to determine whether adolescent exposure to alcohol leads to long‐term structural and functional changes that are manifested in adult neuronal circuitry. Methods We specifically focused on hippocampal area CA1, a brain region associated with learning and memory. Using electrophysiological, immunohistochemical, and neuroanatomical approaches, we measured post‐AIE changes in synaptic plasticity, dendritic spine morphology, and synaptic structure in adulthood. Results We found that AIE‐pretreated adult rats manifest robust long‐term potentiation, induced at stimulus intensities lower than those required in controls, suggesting a state of enhanced synaptic plasticity. Moreover, AIE resulted in an increased number of dendritic spines with characteristics typical of immaturity. Immunohistochemistry‐based analysis of synaptic structures indicated a significant decrease in the number of co‐localized pre‐ and postsynaptic puncta. This decrease is driven by an overall decrease in 2 postsynaptic density proteins, PSD‐95 and SAP102. Conclusions Taken together, these findings reveal that repeated alcohol exposure during adolescence results in enduring structural and functional abnormalities in the hippocampus. These synaptic changes in the hippocampal circuits may help to explain learning‐related behavioral changes in adult animals preexposed to AIE.